Upper Limbs Muscle Co-contraction Changes Correlated With the Impairment of the Corticospinal Tract in Stroke Survivors: Preliminary Evidence From Electromyography and Motor-Evoked Potential - Sheng, Wenfei; Li, Shijue; Zhao, Jiangli; Wang, Yujia; Luo, Zichong; Lo, Wai Leung Ambrose; Ding, Minghui; Wang, Chuhuai; Li, Le (Frontiers in Neuroscience, 2022)
Objective: Increased muscle co-contraction of the agonist and antagonist muscles during voluntary movement is commonly observed in upper limbs of stroke survivors. Much remain to be understood about the underlying mechanism. The aim of the study is to investigate the correlation between increased muscle co-contraction and the function of the corticospinal tract (CST). Methods: Nine stroke survivors and nine age-match healthy individuals were recruited. All the participants were instructed to perform isometric maximal voluntary contraction (MVC) and horizontal task which consist of sponge grasp, horizontal transportation and sponge release. We recorded electromyographic (EMG) activities from four muscle groups during the MVC test and horizontal task in upper limbs of stroke survivors. The muscle groups consist of extensor digitorum (ED), flexor digitorum (FD), triceps brachii (TRI) and biceps brachii (BIC). The Root Mean Square (RMS) of EMG was applied to assess the muscle activation during horizontal task. We adopted a co-contraction index (CI) to evaluate the degree of muscle co-contraction. Corticospinal tract function was evaluated by the motor evoked potentials (MEP) parameters including resting motor threshold, amplitude, latency, and central motor conduct time. We employed correlation analysis to probe the association between CI and MEP parameters. Results: The RMS, CI and MEP parameters on the affected side showed significant difference in comparisons with the unaffected side of stroke survivors and healthy group. The result of correlation analysis showed CI was significantly correlated with MEP parameters in stroke survivors. Conclusion: There existed increased muscle co-contraction and impairment in CST functionality on the affected side of stroke survivors. The increased muscle co-contraction was correlated with the impairment of the CST. Intervention which could improve the excitability of the CST may contribute to the recovery of muscle discoordination in upper limbs of stroke survivors.